The "Gesit" E-Book on Improving Teenagers' Knowledge and Attitudes toward Obesity Management - Novianti, Siti; Nadhifah, Tahani Nisrina; Gustaman, Rian Arie; Lina, Nur Lina (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Indonesia faces a triple burden of nutritional problems, including the rising prevalence of obesity among children and adolescents. Obesity cases among senior high school students in Tasikmalaya Regency were notably high in 2023, indicating the need to analyze factors contributing to obesity in the region. This study aimed to analyze the effect of an e-booklet on obesity management on the knowledge and attitudes of obese adolescents at SMK Singaparna and SMK Daaruddakwah. A quantitative pre-experimental method with a one-group pretest–posttest design was used, and hypothesis testing was conducted using the Wilcoxon test and paired t-test. The sample consisted of 42 obese adolescents selected through total sampling. The results showed an increase in knowledge (6,21 points) and attitudes (1,91 points) regarding obesity management, indicating a significant effect of the e-booklet on improving knowledge (p-value< 0,001) and attitudes (p-value = 0,011). It is recommended that the developed e-booklet be utilized as a health promotion medium for obesity management.